Coping with Capital Inflows : Experiences of Selected European Countries - Vavra, David; Otker, Inci.; Polanski, Zbigniew; Topf, Barry (Washington, D.C. : International Monetary Fund, 2007)
This paper reviews the experiences of a number of European countries in coping with capital inflows. It describes the nature of the inflows, their implications for macroeconomic and financial stability, and the policy responses used to cope with them. The experiences suggest that as countries become more integrated with international financial markets, there is little room to regulate capital flows effectively. The most effective ways to deal with capital inflows would be to deepen the financial markets, strengthen financial system supervision and regulation, where needed, and improve the capacity to design and implement sound macroeconomic and financial sector policies. These actions will help increase the absorption capacity and resilience of the economies and financial systems to the risks associated with the inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet